Shaking and other non-accidental head injuries in children - Minns, R. A. (Robert Anthony); Brown, J. Keith (Clinics in developmental medicine, 2005)
Presents information on shaken baby syndrome. Covering the diagnosis, the long-term disability that results which is also associated with a high degree of life-long physical and intellectual disability.